Consumer reaction: linking consumer associations and cultural values - Orangzab; Suleman Aziz Lodhi; Muhammad Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
Brand is one of the most important resources of the company. It contains worth not only for the company but also for the consumers. The objective of this study is to examine the effect of brand associations on consumer reaction, brand associations are separated into personal and social association, further how the cultural values of the consumers affect the associations and consumer response relationship. Mix method research is used in this research, starting with the qualitative research for theory (framework) development and then followed by quantitative research for testing theory for the purpose of enhancing generalizability of the framework. The transportation sector is considered for testing the conceptual framework. Data is collected from passengers through survey method. The result of this research shows that both personal and social associations have positive impact on consumer reaction and cultural values play moderating role in this relationship. Specifically, masculinity and uncertainty avoidance play moderating role between social associations and consumer response relationship while collectivism plays moderating role between the personal associations and consumer response relationship. This study will help the brand managers to identify how cultural values influence the consumer reaction, which associations are contributing towards desired consumer reaction and which associations need to be reinforced.
Keywords: 330; personal associations; social associations; consumer reaction; cultural values; transportation sector